Determinan dari Kecemasan Ibu dalam Memiliki Alat Kontrasepsi - Indra Iswari; Ida Samidah; Berlian Kando Sianipar (Jurnal Keperawatan Silampari, 2022)
The purpose of this study was to discover the factors that contribute to a mother's anxiety. The study employed a cross-sectional design, with the outcome being a mother's anxiety. There were 398 respondents who were mothers, had lived in Bengkulu City for at least three years, and were willing to be a respondent. The total was computed using simple random sampling. The result showed that the variables had conclusive significant with outcome included income (AOR: 6.7, 95%CI: 3.07-14.69, p-value: <0.001), perception (AOR: 3.04, 95%CI: 1.1 – 8.4, p-value: 0.032), health literacy ((AOR: 2.97, 95%CI: 2.1 – 4.3, p-value: <0.001), stress ((AOR: 2.3, 95%CI: 1.1 – 4.9, p-value: 0.031), and education (AOR: 1.8, 95%CI: 1.1 – 2.8, p-value: 0.018). The good one program should be released as soon as possible to assist them in selecting the appropriate contraception that will help them avoid side effects. Keywords: mother’s anxiety, health literacy, perception, stress